Acupuntura e implante de fragmentos de ouro em pontos de acupuntura e pontos gatilho para o tratamento de displasia coxo-femoral em pastor alemão - Scognamillo-Szabó, Marcia Valeria Rizzo [UNESP]; de Sousa, Nicole Ruas; Carvalho, Lílian Tannús [UNESP]; Carvalho, Francisco Sales Resende (My University, 2010)
Background: Canine hip dysplasia (HD) is characterized by hip joint laxity and subluxation. It is the most common cause of osteoarthritis in dogs, especially in larger breeds. Its management includes nutritional supplements, nonsteroidal anti-inflammatory drugs, physical therapy, acupuncture or surgical procedures. Implantation of gold beads in acupuncture points and trigger points around a joint has been used in the treatment of osteoarthritis in dogs for at least 30 years. Gold bead implants(GBI) acts as continuous acupuncture stimulation and trigger point treatment in canine HD with long lasting results. Electrophysiological investigations of trigger points reveal dysfunctional muscle spindles which indicate that the electrical activity of active loci arises from extrafusal motor endplates. Case: This is a report on the use of acupuncture and GBI for bilateral HD in a nine year old female German Shepherd. The patient has a HD non-responsive to anti-inflammatory drugs and was unable to stand up or walk by its own. Radiographs showed marked dysplasia, significant subluxation with the femoral head partly out of a shallow acetabulum and massive secondary arthritic bone changes, mainly on the right side. The animal was submitted to eight acupuncture sessions with seven days interval. After the first acupuncture session the use of NSAID was interrupted. After eight weeks the dog was considered rehabilitated and underwent GBI in acupoints and trigger points as maintenance treatment. During the one-year follow-up period the improvement remained unchanged with no need of analgesics. Discussion: It has been suggested that acupuncture or GBI can treat the chronic pain resulting from osteoarthritis induced by HD. According to AP theory, GBI is permanent and long-lasting acupoint stimulation. Moreover, the method is inexpensive, quick and easy to perform, with no postoperative pain or need of exercise restriction. Although gold is extremely corrosionresistant, the surface of the gold implants stimulates a reaction from the immune system causing an oxidative liberation of gold ions with anti-inflammatory actions. It is well known that gold ions are effective inhibitors of the respiratory burst of neutrophils and monocytes and the proliferation of lymphocytes. These findings suggest that gold implantation, on a local scale, mimics the anti-inflammatory and pain-relieving effect of drugs with chemically bound gold ions. The relatively slow speed of the process results in a limited liberation of gold ions securing that they are taken up almost exclusively by cells close to the implant. The nine year old female German shepherd had a positive response to acupuncture with pain relieve and locomotor rehabilitation. For the nine year old female German shepherd previous acupuncture sessions to GBI resulted in no post-implant worsening period. Indeed, the association acupuncture/GBI does not have the anti-inflammatory drugs undesirable effects and brings long lasting results. In conclusion, GBI therefore should be considered for canine HD when conservative or medical treatments fail to give the desired effect.
Acupuncture and gold bead implant for hip dysplasia in German Shepherd
Keywords: Dog; Metal implant; Miofascial pain. arthrosis; Traditional chinese medicine